The grammarian, the geometrician and the shapes of desire - Ochoa, Daniel (2023)
This document discusses about utopias as a cultural resource fully loaded with desires and ambitions. Its analysis enables us to interpret the human condition and our symbolic world. On the one hand, this text examines the underlaying motivations of these kinds of models; on the other hand, it explores the consequences of utopia’s embodiment in the real world. The purpose of this article is to reflect on the role of utopias throughout the history of thought.